Diagnosis and Management of Chylous Ascites - Prihastuti, Putu Shely; Wibawa, I Dewa Nyoman (The Indonesian Society for Digestive Endoscopy, 2023)
Chylous ascites (CA) is a rare form of ascites that results from the leakage of lipid-rich lymph into the peritoneal cavity. This usually occurs due to trauma and rupture of the lymphatics or increased peritoneal lymphatic pressure secondary to obstruction. The underlying etiologies for CA have been classified as traumatic, congenital, infectious, neoplastic, postoperative, cirrhotic or cardiogenic. Since malignancy and cirrhosis account for about two-thirds of all the cases of CA in Western countries. The diagnosis of CA is based on the distinct characteristic of the ascitic fluid which includes a milky appearance and a triglyceride level of 200 mg/dL. The management consists of identifying and treating the underlying disease process, dietary modification, and diuretics. Treatment with nutritional optimization and management of the underlying etiology are the cornerstones of therapy. When conservative measures fail, other interventions such as octreotide/somatostatin analogues, surgical ligation, embolization and transjugular intrahepatic portosystemic shunt in patients with cirrhosis can be considered.